PENGARUH E-SERVICE QUALITY DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PENGGUNA APLIKASI DANA - Wisnu Mahendri; Ifta Nur Azah (Gapenas Publisher, 2023)
In today's digital era, many people choose to use a digital wallet as a payment transaction tool because it makes it easier to carry out transaction activities. One of the digital wallets that is widely used by the public is the DANA digital wallet, which can help with transactions needed by customers. The purpose of this study was to determine the effect of electronic service quality and customer relationship management (CRM) on customers using the DANA digital wallet in Jombang. The method used in this study is a quantitative method with data analysis techniques in the form of descriptive analysis, multiple linear regression analysis, and classical assumption test. The results of this study are that service quality affects customer loyalty for DANA users in Jombang because with fast and effective service quality, users will more often use digital wallets as a means of payment transactions. CRM also affects customer loyalty for DANA digital wallet users in Jombang because there is a guarantee of security for user balances, thereby generating customer trust and loyalty